Diagnosis and management of food allergy in children. Issue 7 (July 2016) - Luyt, David; Ball, Heidi; Kirk, Kerrie; Stiefel, Gary
Abstract: Food allergy (FA) in children is common, affecting about 6% of children in the UK, and is thought to be increasing in prevalence. Presentation varies widely with age, causative food, type of FA (IgE-mediated or non-IgE mediated) and severity. Assessment of suspected FA includes a detailed clinical history and dietary history and appropriate confirmatory allergy testing. The traditional management of complete dietary exclusion of the causative and related foods is evolving to one of limiting exclusion and early reintroduction. Novel treatments under investigation are mechanisms to prevent FA and oral desensitisation in selected cases in an attempt to cure FA. This article aims to give advice to the generalist about how to assess and initiate appropriate investigation a child presenting with possible food allergy.